Analysis of the Level of E-Government Implementation and Factors That Influence It (Empirical Study of Regional Government in Central Java) - Dwi Winarni; Ilham Nuryana Fatchan; Rifka Utami Arofah (Jurnal Akuntansi, 2023)
The new public management is an attempt by the government to improve public accountability, transparency, and more effective and efficient performance. The application of e-Government is an innovation by local governments to realize the achievement of new public management. Not only has the aim of transparency and accountability, the use of the e-Government application system is also expected to be able to improve the performance of local governments with the principle of value for money. The purpose of this study is to analyze the factors that influence the implementation of e-Government in the Regional Government of Central Java and the relationship of each of these factors to the implementation of e-Government. The research was conducted using quantitative research methods with data analysis using EViews. The results show that local revenue (PAD) has a positive effect on the level of implementation of e-Government, spending capital has no effect on e-Government implementation, local government financing has a positive effect on e-Government implementation, regional per capita income (PDRB) has no effect on implementation e-Government, the level of public education has no effect on e-Government, and the population has no effect on the implementation of e-Government.